2022
DOI: 10.3390/tropicalmed7080147
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Awareness of Sexually Transmitted Infections (STIs) and Prevalence of STIs among Sub-Saharan African Men and Women

Abstract: Treatments for HIV and other STIs are not readily available in sub-Saharan Africa and other resource-limited areas, where the prevalence of HIV and other STIs is high. In the absence of treatment and laboratory infrastructure to monitor treatment efficacy, increasing awareness of STIs and STI screening are crucial components of STI prevention programs. In the current study, we sought to estimate the awareness of STIs in resource-limited countries and evaluate the strength of the association between the awarene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Similar to other reported research findings, 16,30,40,41,48 our study revealed that multiple infections were quite common, occurring in more than half (59%) of the participants. These multiple infections involved various pathogens, including CT, UU, UP, MH and MG; and specifically, CT infection that was often found to occur with UU, UP, MG, and MH infections.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to other reported research findings, 16,30,40,41,48 our study revealed that multiple infections were quite common, occurring in more than half (59%) of the participants. These multiple infections involved various pathogens, including CT, UU, UP, MH and MG; and specifically, CT infection that was often found to occur with UU, UP, MG, and MH infections.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings consolidate the argument of the extent of effectiveness of the syndromic approach for STI management in LMICs, especially in SSA. 1,40,41 At present, WHO recommends the use of point-of-care test for STIs which is either rapid or molecular, and that is cost-effective and affordable in LMICs like Tanzania. 2,42,43 Importantly, accurate detection and effective treatment are essential in reducing the transmission and impact of these infections for individuals affected by STIs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor period education results in a lack of knowledge about menstrual cycle norms; menstrual hygiene; gynecological conditions and their symptoms; and sexual health (eg, contraception and STIs). Specifically, according to the World Bank classification, LMICs have the highest prevalence of STIs (eg, gonorrhea, trichomoniasis, and syphilis), and the awareness of STIs other than HIV in those countries is very low [ 74 - 76 ]. Therefore, menstrual and sexual health apps, together with systemic governmental and societal education efforts, can mitigate long-term repercussions of poor health literacy, thereby decreasing unfavorable health outcomes such as infertility, abortions, preterm delivery, and perinatal and neonatal morbidities and helping with cutting health care costs associated with STI treatment [ 77 - 80 ].…”
Section: Discussionmentioning
confidence: 99%